Cryo-EM studies of the structure and dynamics of vacuolar-type ATPases - Mazhab-Jafari, Mohammad T. (Sci Adv, 2016)
Electron cryomicroscopy (cryo-EM) has significantly advanced our understanding of molecular structure in biology. Recent innovations in both hardware and software have made cryo-EM a viable alternative for targets that are not amenable to x-ray crystallography or nuclear magnetic resonance (NMR) spectroscopy. Cryo-EM has even become the method of choice in some situations where x-ray crystallography and NMR spectroscopy are possible but where cryo-EM can determine structures at higher resolution or with less time or effort. Rotary adenosine triphosphatases (ATPases) are crucial to the maintenance of cellular homeostasis. These enzymes couple the synthesis or hydrolysis of adenosine triphosphate to the use or production of a transmembrane electrochemical ion gradient, respectively. However, the membrane-embedded nature and conformational heterogeneity of intact rotary ATPases have prevented their high-resolution structural analysis to date. Recent application of cryo-EM methods to the different types of rotary ATPase has led to sudden advances in understanding the structure and function of these enzymes, revealing significant conformational heterogeneity and characteristic transmembrane α helices that are highly tilted with respect to the membrane. In this Review, we will discuss what has been learned recently about rotary ATPase structure and function, with a particular focus on the vacuolar-type ATPases.